Rancang Bangun Piranti Lunak Sistem Informasi Pendukung Pengujian Terowongan Angin Kecepatan Rendah Indonesia - Ivransa Zuhdi Pane (Ultimatics : Jurnal Teknik Informatika, 2014)
Wind tunnel test in Indonesian Low Speed Tunnel required a supportive information system which be able to monitor various test activities and record numerous test conditions in an integrated manner. The software of such information system is engineered to realize information technology based support into the test execution through rapid cycles of analysis, design and implementation phases. Built software was expected to increase the performance of overall wind tunnel test management. Index Terms - wind tunnel test, information system, test model, software engineering